Dumfriesshire, Großbritannien: Landschaftsarchäologische Untersuchungen an zwei Fundstellen in Südschottland - Posluschny, Axel G. (e-Forschungsberichte des DAI, 2023)
The research project in Dumfriesshire aimed to survey two Iron Age and Roman sites and their immediate environs near Lockerbie (Scotland, United Kingdom). With the help of a magnetic survey and soil sampling (coring) in selected areas of the sites a team from the Romano-Germanic Commission investigated the sites of Burnswark (indigenous hillfort and fortlet, Roman siege or training camps) and Ladyward (Roman Fort) to prepare a larger research project, which will deal with the confrontation, cooperation or collaboration of indigenous societies and the Roman occupiers in Scotland between Hadrian’s and Antonine’s Wall in the late first and second century AD from a landscape archaeological perspective.